Aqueous extract of clove inhibits tumor growth by inducing autophagy through AMPK/ULK pathway. (16th April 2019) - Li, Cong; Xu, Huanli; Chen, Xiaoliang; Chen, Jijun; Li, Xiao; Qiao, Gan; Tian, Ye; Yuan, Ru; Su, Shuonan; Liu, Xiaohui; Lin, Xiukun
Abstract : Cloves ( Syzygium aromaticum ), a traditional Chinese medicinal herb, displays broad biological activity. In the present study, the aqueous extract of clove (AEC) was prepared, and its anticancer affects were studied. 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2 H ‐tetra‐zolium (MTS) analysis revealed that AEC was able to inhibit cancer cell growth in vitro on several cancer cell lines; the IC50 is around 150 μg/ml for human pancreatic ASPC‐1 and human colon HT‐29 cancer cells. Treatment of the cancer cells with AEC also diminished the colony formation significantly in both human pancreatic ASPC‐1 cancer cells and human colon HT‐29 cancer cells. In vivo study revealed that AEC inhibited the tumor growth significantly in HT‐29 xenograft mice model. Transmission electron microscope, flow cytometry assay, and fluorescence microscope analysis confirmed that AEC is capable of inducing cell autophagy. Further study showed that AMPK/ULK pathway plays an important role in AEC‐induced autophagy in cancer cells. Analysis of AEC components was performed by liquid chromatograph mass spectrometer approach, and more than nine constitutes were identified in AEC fraction. The study provides evidence that AEC has potential to be developed as a novel anticancer agent or as an adjuvant in cancer chemotherapy.